2009
DOI: 10.5458/jag.56.185
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Starch Characteristics on Digestibility of Steamed Rice Grains under Sake-making Conditions,and Rapid Estimation Methods of Digestibility by Physical Analysis

Abstract: Retrogradation of starch in steamed rice grains under sake-making conditions was examined. The enthalpy change derived from retrogradation of amylopectin increased during the koji and sake mash processes. Ethanol in the sake mash accelerated retrogradation of amylopectin. Enzyme digestibility and properties of endosperm starches of 136 Japanese rice samples used for sake production were examined. A digestion test of steamed rice grains was conducted after 24 h storage at 15 C to estimate more accurately digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…3,38) The group of high-amylose starches had different SLC contents of amylopectin, different peak viscosities and setback (SB) values (we use the term "consistency" for "SB" in the this paper) according to the measurements using a RVA. 39,40) RVA appears to be a useful tool for the rapid and simple evaluation of amylose contents or chain length distribution of amylopectin, while it was relatively expensive.…”
mentioning
confidence: 99%
“…3,38) The group of high-amylose starches had different SLC contents of amylopectin, different peak viscosities and setback (SB) values (we use the term "consistency" for "SB" in the this paper) according to the measurements using a RVA. 39,40) RVA appears to be a useful tool for the rapid and simple evaluation of amylose contents or chain length distribution of amylopectin, while it was relatively expensive.…”
mentioning
confidence: 99%
“…These results suggest that the ambient temperature likely affects the varietal characteristics of the starch properties associated with the gelatinization temperature during the maturation period. A similar relationship between the ambient temperature during the maturation period and the gelatinization temperature was also reported in rice starch (Asaoka et al, 1984;Okuda et al, 2009) and amylose content in rice grains (Resurreccion et al, 1977;Sano et al, 1985;Yamakawa et al, 2007). It was reported that the fine structure of amylopectin changed with ambient temperature during the maturation period together with gene expression patterns and enzyme activity levels associated with starch synthesis (Inouchi et al, 2000;Jiang et al, 2003;Umemoto et al, 1999;Yamakawa et al, 2007).…”
Section: Variability In Starch Properties Under Different Ambient Temmentioning
confidence: 59%
“…40) Okuda et al showed that the pasting temperature of milled rice as measured by RVA correlated well with the ratio of short-to-long chain amylopectin and with enzyme digestibility. 35) Correlation between AAC, RS, and pasting properties of 38 Japonica polished rice samples AAC showed a positive correlation with SB (r = 0.76) and SB/Con ratios (r = 0.76) at p < 0. Formula for estimating the AAC based on the pasting properties of Japonica polished rice Fig.…”
Section: Pasting Properties Of Japonica Polished Rice Flourmentioning
confidence: 94%
“…3,34) For many years, the SB, defined by subtracting the viscosity at the trough from the final vis., has been related to the firmness and the amylose content of the rice, and BD, defined by subtracting the viscosity at the trough from the viscosity at the peak, has been related, too. 35) We here characterized the Japonica polished rice and starch; evaluated the relationship between their pasting properties, AAC and RS. The improvements, which we performed for analyzing the pasting properties measured by RVA and, the novel estimation formulae, which we developed in the present paper against the AAC and RS, would lead to an easy and rapid method for clarifying starch characteristics.…”
mentioning
confidence: 99%